Metabolic characterization of imatinib-resistant BCR-ABL T315I chronic myeloid leukemia cells indicates down-regulation of glycolytic pathway and low ROS production. Issue 9 (1st September 2016) - Ko, Byung Woong; Han, Jeongsu; Heo, Jun Young; Jang, Yunseon; Kim, Soo Jeong; Kim, Jungim; Lee, Min Joung; Ryu, Min Jeong; Song, Ik Chan; Jo, Young Suk; Kweon, Gi Ryang
Abstract: Long-term imatinib treatment induces drug-resistant chronic myeloid leukemia (CML) cells harboring T315I gate keeper mutation of breakpoint cluster region (BCR)-ABL oncogenic kinase. However, although cell proliferation is coupled with cellular energy status in CML carcinogenesis, the metabolic characteristics of T315I-mutant CML cells have never been investigated. Here, we analyzed cell proliferation activities and metabolic phenotypes, including cell proliferation, oxygen consumption, lactate production, and redox state in the KBM5 (imatinib-sensitive) and KBM5-T315I (imatinib-resistant) CML cell lines. Interestingly, KBM5-T315I cells showed decreased cell proliferation, lactate production, fatty acid synthesis, ROS production, and down regulation of mRNA expression related to ROS scavengers, such as SOD2, catalase, GCLm, and GPx1. Taken together, our data demonstrate that the lower growth ability of KBM5-T315I CML cells might be related to the decreased expression of glycolysis-related genes and ROS levels, and this will be used to identify therapeutic targets for imatinib resistance in CML.